2021
DOI: 10.1002/admi.202001882
|View full text |Cite|
|
Sign up to set email alerts
|

Effective Pretreatment Routes of Polyethylene Terephthalate Fabric for Digital Inkjet Printing of Enzyme

Abstract: A major number of studies used enzymes during pre-processing in the form of beads, pellets, otherwise during post-processing, for example, surface cleaning and effluent treatment. [2,3] A few studies used flat film and paper like supports, however, use of non-flat textile like surfaces for immobilization is very limited. [4] Textile fabrics can be a more suitable support for enzyme immobilization due to their inherent advantages of being strong, flexible, and lightweight, along with providing low pressure drop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…CMC based ink retained higher activity (69%) than PVA based ink (52%) when compared to respective activity before printing. As observed for piezoelectric printing of other proteins 28 , 37 , such reduction of activity could be caused by shear stress generated inside the printhead during drop ejection to influence tyrosinase protein structure. Activity difference between CMC and PVA based inks might be related to the solvent composition which can interfere with the electrostatic forces governing protein conformation 38 .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…CMC based ink retained higher activity (69%) than PVA based ink (52%) when compared to respective activity before printing. As observed for piezoelectric printing of other proteins 28 , 37 , such reduction of activity could be caused by shear stress generated inside the printhead during drop ejection to influence tyrosinase protein structure. Activity difference between CMC and PVA based inks might be related to the solvent composition which can interfere with the electrostatic forces governing protein conformation 38 .…”
Section: Resultsmentioning
confidence: 96%
“…amount of feed gas, electric power) need to be optimized. Nominal reduction of tensile strength values (1–2%) was observed after plasma treatment as this process is known to be less detrimental to the bulk properties of the fibre 24 , 27 , 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Nominal reduction of tensile strength values (1-2%) was observed after plasma treatment as this process is known to be less detrimental for the bulk properties of the bre. 23,26,27 Ink formulation…”
Section: Resultsmentioning
confidence: 99%
“…The washing durability of flame retardant PET fabrics is essential for their application. Generally, because of a lack of polar or chemically active groups, it is difficult to obtain durable functional PET fibers without the help of enzymatic pretreatment, 43 plasma pretreatment 44 or photo-induced grafting. 45 In this study, the washing durability results of hybrid coated PET fabrics are as shown in Figure 11.…”
Section: Resultsmentioning
confidence: 99%